2020
DOI: 10.1002/aur.2354
|View full text |Cite
|
Sign up to set email alerts
|

Developmental–behavioral profiles in children with autism spectrum disorder and co‐occurring gastrointestinal symptoms

Abstract: Gastrointestinal (GI) symptoms are frequently reported in children with autism spectrum disorder (ASD). We evaluated the frequency and severity of GI symptoms in preschool-aged children with ASD compared to participants with typical development (TD). Our goal was to ascertain whether GI symptoms are associated with differences in sex or developmental and behavioral measures. Participants were between 2 and 3.5 years of age and included 255 children with ASD (184 males/71 females) and 129 age-matched TD control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0
8

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(66 citation statements)
references
References 45 publications
(69 reference statements)
3
55
0
8
Order By: Relevance
“…Eating and feeding problems might in children with ASD, as in all children, be due to and/or connected to different medical causes such as food allergy, gastrointestinal disorders, disorders in oral and nasopharyngeal function, and congenital heart diseases or neurological disorders. Studies have reported a higher prevalence of gastrointestinal diseases, food allergies, and medical co-morbidities in general in children with ASD than in typically developing children (31)(32)(33). ADHD and other neurodevelopmental coexisting disorders might also affect feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Eating and feeding problems might in children with ASD, as in all children, be due to and/or connected to different medical causes such as food allergy, gastrointestinal disorders, disorders in oral and nasopharyngeal function, and congenital heart diseases or neurological disorders. Studies have reported a higher prevalence of gastrointestinal diseases, food allergies, and medical co-morbidities in general in children with ASD than in typically developing children (31)(32)(33). ADHD and other neurodevelopmental coexisting disorders might also affect feeding.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly concerning because it may be more challenging for autistic children to verbalize or communicate physical pain, leading to lack of appropriate medical care. Within the APP, we evaluated parent-reported GI symptoms at Time 1 and identified a subgroup comprising 48% of autistic children who experience significant GI problems ( Restrepo et al, 2020 ). Children with significant GI problems also had higher levels of self-injurious behaviors, restricted stereotyped behaviors, sensory sensitivities, aggressive behavior, attention problems, as well as sleep problems such as shorter sleep duration, night awakenings, and parasomnia.…”
Section: Subgrouping By Other Biological Characteristicsmentioning
confidence: 99%
“…According to the Diagnostic and Statistical Manual of Mental Disorders, 5th edition, ASDs are characterized by deficits in social communications and the presence of restricted interests and repetitive behaviors, including four separate disorders: autistic disorder, Asperger's syndrome, childhood disintegrative disorder and the catch-all diagnosis of pervasive developmental dis order not otherwise specified [29]. Many studies have demonstrated that children with ASD suffer frequently from gastrointestinal symptoms, such as diarrhea, constipa-tion, abdominal pain or gaseousness, mainly children with ASD and increased problem behaviors, such as social withdrawal, sleep problems and self-injuries [30,31]. According to a meta-analysis, children with ASD have three times higher risk of gastrointestinal symptoms compared to children without ASD [32].…”
Section: Asdsmentioning
confidence: 99%